The Associations Between Parental Knowledge and Parental Difficulties in Emotional Regulation with Children’s Social Competence - Yin, Lifeng (My University, 2024)
In an increasingly complex and fast-paced world, children’s social competence is critical to them to optimistically and effectively coordinate their relationships with others, to adapt to the development of the society. However, the development of children’s social competence cannot be separated from their families, especially the influence of parents, whose mastery the knowledge of child development and understanding and cognition of their own emotions are important factors affecting parental practice. In the process of children’s growth, how parents respond to children’s needs according to their knowledge and emotional regulation ability could affect the formation of a benign family environment, thus providing support for children’s overall development. With limited studies regarding parental knowledge of child development in China compared to studies in western countries. This paper discusses the complex relationship between parents' knowledge, parents' emotional regulation difficulties and children's social competence on the premise of the Chinese environment. On the basis of theoretical background review, this research applies qualitative approach to collect data, with the primary goal of investigating in the relationships between parental knowledge, emotional regulation difficulties and children’s social competence. Using convenient sampling, 201 parents from a kindergarten in Lincang City, Yunnan Province, China, participated in answering an online questionnaire that combined with the scales of KIDI-P, DERS, and SCBE-30. Based on parents’ self-report, the statistical analysis results showed: parents’ parental knowledge was at a medium level and difficulties in emotional regulation is low which indicates they could regulate their emotion well, and children generally had a fair good level of social competence. Significant differences were found in some subscales under the influence of demographic traits. Parents’ knowledge of normative behaviours showed significant differences in parents’ educational background; children’s sensitive-cooperation revealed significant differences in both parents’ educational back ground and children’s age; significant differences were found in awareness in terms of parents’ age and educational background; there were also significant differences in impulse and strategies in terms of parental role; and in terms of the child’s status, there were significant differences in goals. The result also found that parental knowledge was negatively correlated to parental difficulties in emotional regulation; parents' difficulties in emotional regulation was negatively correlated to children's social competence. While parental knowledge was positively correlated with children’s social competence.
Keywords: parental knowledge, emotion regulation, children’s social competence